Intersection - ATYP (Intersection Ser., 2020)
Offbeat. Upbeat. Move to your own beat. These are stories that explore the pulsating experience of young lives. Intersection: Beat is a taste-test of Australia's brightest new playwrights illuminating fragments of lives dancing on the edge of adulthood. This collection of short plays will surprise, intrigue, provoke and move. The characters range in age from 15-22 and the production showcases some of the finest young performers.